2019
DOI: 10.1002/lol2.10117
|View full text |Cite
|
Sign up to set email alerts
|

Hot tops, cold bottoms: Synergistic climate warming and shielding effects increase carbon burial in lakes

Abstract: Lakes play a significant role in the global carbon cycle where inputs from watersheds and primary production are either stored in sediments or lost to the atmosphere through respiration. Climate change is anticipated to increase atmospheric losses as water overlying sediments warms, thus reducing carbon storage. Lakes worldwide, however, are not only warming but are also losing transparency through eutrophication or browning. The synergistic result is that heat is trapped in the surface layers of more colored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
79
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 80 publications
5
79
1
Order By: Relevance
“…These are two prominent drivers of long-term decreases in water transparency via eutrophication and browning that would result in greater deepwater and mean water temperature cooling 2,33 in these specific regions but less so in other regions. In a review of 205 lakes that reported deepwater temperature trends, nearly all lakes that had cooling deeper waters also experienced decreasing water transparency primarily due to either eutrophication or browning 45 . However, the lack of time series for in-situ measurements of chlorophyll, DOC, Secchi depth, or other water transparency related variables limit our ability to test this proposed mechanism explicitly for these two lake thermal regions.…”
Section: Discussionmentioning
confidence: 99%
“…These are two prominent drivers of long-term decreases in water transparency via eutrophication and browning that would result in greater deepwater and mean water temperature cooling 2,33 in these specific regions but less so in other regions. In a review of 205 lakes that reported deepwater temperature trends, nearly all lakes that had cooling deeper waters also experienced decreasing water transparency primarily due to either eutrophication or browning 45 . However, the lack of time series for in-situ measurements of chlorophyll, DOC, Secchi depth, or other water transparency related variables limit our ability to test this proposed mechanism explicitly for these two lake thermal regions.…”
Section: Discussionmentioning
confidence: 99%
“…Although periodically acting as CO 2 sinks (Laurion et al ., 2010), thermokarst ponds are often CO 2 and CH 4 oversaturated and thus generally recognized as a significant source of greenhouse gases (GHGs) (Sobek et al ., 2005; Breton et al ., 2009). CH 4 emissions from such ponds account for two‐third of the total emissions in regions above the latitude 50°N (Wik et al ., 2016) and are strongly stimulated by atmospheric warming (Negandhi et al ., 2014; Negandhi et al ., 2016; Bartosiewicz et al ., 2019). However, shallow ponds are still mostly neglected in estimates of regional and global C budgets (Muster et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Because Daphnia plays a vital role in freshwater ecosystems 60 , its fate will have a bearing on the functioning of entire ecosystems. Planktonic organisms that inhabit stratified lakes with deep-water refuges might be less susceptible to the negative consequences of temperature increase 61 , but in the case of shallow polymictic lakes, temperature increase is likely to have far-reaching consequences.…”
Section: Discussionmentioning
confidence: 99%